Analysis of the Causes of Tiktok Shop Closures in Indonesia - Kadek Januarsa Adi Sudharma; Anak Agung Ngurah Bagus Swadharma Sanjaya (Sociological Jurisprudence Journal, 2025)
Advances in digital technology have transformed commerce in Indonesia, and the emergence of e- commerce platforms has created significant challenges to the current legal framework. In this regard, the TikTok Shop phenomenon provides an interesting case study that illustrates the complex interplay between legal compliance and technical innovation. This paper examines the legality and dynamics of e-commerce in Indonesia using TikTok Shop, a social commerce network that was shut down and then resurrected through a merger with Tokopedia. Analyzing the legality of the TikTok shop and determining the reasons for its closure are the main objectives of this research. This research examines a number of laws, including the Electronic Information and Transaction Law, the Job Creation Law, and the Minister of Trade Regulation. This research aims to juridically analyze the existing e-commerce system in Indonesia. Specifically in the case of TikTok Shop, which experienced closure and the return of TikTok Shop after the merger with Tokopedia. and also how the implications for the regulation and practice of e-commerce in Indonesia. Statutory and conceptual methods are part of the normative legal approach. According to the research, TikTok Shop was first shut down due to a number of violations. The violations included purported data piracy, unfair pricing practices, and not having a Trading Through Electronic Systems (PPMSE) license. The platform was able to resume operations in accordance with the law after the merger with Tokopedia. This research uses Gustav Radbruch's theory of legal certainty to investigate the alignment between justice, expediency, and legal certainty. The findings of this research highlight the need for adaptable legislation to keep up with the rapid growth of digital technology. Protection of small and medium-sized enterprises (MSMEs), clear electronic contracts, and creating a robust and competitive e-commerce environment are the main objectives of this study.